2019
DOI: 10.31648/oej.4372
|View full text |Cite
|
Sign up to set email alerts
|

Combining Paid Work and Eldercare in the Netherlands in the Practice of Selected Dutch Organizations

Abstract: The possibility to balance work and eldercare in the Netherlands is determined by legal and institutional factors (such as special employment entitlements for a career in the form of leaves and a flexible working arrangement). In our paper we compare the Dutch legislation in this field with the HRM practice of four Dutch public and private (non-profit and for-profit) organizations. The aim is to check what kind of workplace eldercare assistance is provided by the organizations and what forms are applied due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…In addition, a wide range of studies further found that the allocation of eldercare prioritizes different factors in different countries. For instance, homecare services in the Netherlands were mainly based on client characteristics such as financial situation, and availability of residential care (Furmańska-Maruszak & Heeger-Hertter, 2019). Studies carried out in the Czech Republic (Souralová & Šlesingerová, 2017) and Poland (Wojciech, 2018) were concerned about the quality of and needs for services provided at home.…”
Section: Homecarementioning
confidence: 99%
“…In addition, a wide range of studies further found that the allocation of eldercare prioritizes different factors in different countries. For instance, homecare services in the Netherlands were mainly based on client characteristics such as financial situation, and availability of residential care (Furmańska-Maruszak & Heeger-Hertter, 2019). Studies carried out in the Czech Republic (Souralová & Šlesingerová, 2017) and Poland (Wojciech, 2018) were concerned about the quality of and needs for services provided at home.…”
Section: Homecarementioning
confidence: 99%
“…In 'Fair Working Conditions for Workers Providing Informal Care for the Elderly in Poland and in the Netherlands', Agnieszka Furmańska-Maruszak and Susanne Heeger also depart from the EPSR, in particular Principle 9 covering 'fair working conditions in balancing work and life'. The authors zoom in on a particular group of workers which is numerically quite large, 33 , by dividing migrants into different categories according to their residence permits and granting highly unequal access to social benefits to these different categories of migrants. This may be exacerbated at the national level, as is the case in Italy the authors argue, creating 'multilayered fragmentation'.…”
Section: The Articles In This Special Issue and Cross-cutting Themesmentioning
confidence: 99%